Secondary school English education in Asia : from policy to practice - Spolsky, Bernard; Sung, Kiwan (Abingdon, Oxon : Routledge, 2015)
'Continuing on from the previously published Primary School English-Language Education in Asia: From Policy to Practice (Moon & Spolsky, 2012), this book compiles the proceedings which took place at the 2011 annual conference of AsiaTEFL which took place in Seoul, Korea. It surveys the current status, practices, challenges, and future directions of Secondary English education in 11 diverse countries - in Israel, Japan, Korea, Singapore, Bangladesh, India, Indonesia, Malaysia, Pakistan, Vietnam and China. Given the importance of secondary English education as the central feature for continuing development of target language and culture in English language teaching in Asia, each contributed chapter includes key policies, theories, and practices related to the development and implementation of country-specific curricular and instructional programs in secondary English educational contexts in these countries. Secondary School English Education in Asia: From Policy to Practice critically analyses both sides of the English language debate -- from advantages to complications -- in its chapters including:Educating for the 21st Century: The Singapore ExperienceMiles to Go : Secondary Level English Language Education in IndiaEnglish Language Education Innovation for the Vietnamese Secondary School: The Project 2020Exploring the Value of ELT as a Secondary School Subject in China: A Multi-goal Model for English CurriculumSecondary School English Education in Asia will appeal to English Language Teaching (ELT) researchers, teacher educators, trainee teachers and teachers, primarily those teaching in Asia'--
'Continuing on from the previously published Primary School English-Language Education in Asia: From Policy to Practice (Moon & Spolsky, 2012), this book compiles the proceedings which took place at the 2011 annual conference of AsiaTEFL which took place in Seoul, Korea. It surveys the current status, practices, challenges, and future directions of Secondary English education in 11 diverse countries - in Israel, Japan, Korea, Singapore, Bangladesh, India, Indonesia, Malaysia, Pakistan, Vietnam and China. Given the importance of secondary English education as the central feature for continuing development of target language and culture in English language teaching in Asia, each contributed chapter includes key policies, theories, and practices related to the development and implementation of country-specific curricular and instructional programs in secondary English educational contexts in these countries. Secondary School English Education in Asia: From Policy to Practice critically analyses both sides of the English language debate - from advantages to complications - in its chapters including: - Educating for the 21st Century: The Singapore Experience - Miles to Go ...: Secondary Level English Language Education in India - English Language Education Innovation for the Vietnamese Secondary School: The Project 2020 - Exploring the Value of ELT as a Secondary School Subject in China: A Multi-goal Model for English Curriculum Secondary School English Education in Asia will appeal to English Language Teaching (ELT) researchers, teacher educators, trainee teachers and teachers, primarily those teaching in Asia'--
Conference proceedings.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching (Secondary) -- Asia -- Congresses; Education and state -- Asia -- Congresses